Analysis of Consumer Behavior on Demand for Hydroponic Vegetables at Fris Fresh Market in Ambon City. - Remesya Miquella Stefhanie Birahy; A.E Pattiselano; W.B Parera, Sp, M.P (Cita konsultindo, 2023)
This study aims to determine consumer behavior based on attributes, size, freshness, cleanliness and benefits) on the demand for hydroponic vegetables and to determine the factors that influence the demand for hydroponic vegetables based on the characteristics of respondents at Fris Fresh Market, Ambon City. This study used a descriptive method where data was collected using a survey technique using an interview measurement tool in the form of a questionnaire containing a list of questions. The results of the study describe the size attribute that has the strongest influence with the highest percentage among the other attributes for respondents in purchasing hydroponic vegetables and simultaneously age, education, number of dependents, income,